Using the CLB in WorkLINC - Beaulne, Audrey (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2020)
Striving for greater English proficiency and securing a job are common goals of newcomers to Canada. For newcomers in the Language Instruction for Newcomers to Canada (LINC) program, the Canadian Language Benchmarks (CLB)/Niveaux de competence linguistique canadiens (NCLC) provide an indicator of their abilities and progress in their language acquisition. The CLB have become the backbone of WorkLINC, an industry-specific work readiness program. They anchor curriculum, Portfolio-Based Language Assessment (PBLA) real-world tasks, and classroom activities. WorkLINC participants develop their vocabulary, soft skills, workplace safety knowledge, and get employment support. Instructors have shared the CLB with employers and community partners to increase comprehension of newcomers’ language levels. Though there are challenges meeting the diverse needs in multi-level cohorts, engaging learners about the purpose of classroom tasks and understanding the CLB competency areas in which they need development enables them to focus on achievable goals directly related to their employment aspirations.